STUDI EKSPERIMENTAL PERILAKU PELAT BETON SERAT BAJA DIATAS PASIR - Sutomo, Yogi Ilham; Supriyadi, Asep; Budi, Gatot Setya (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
At this time the use of concrete is very rapidly growing on the construction activities, because the concrete has the advantages easily formed according to desire, have a good compressive strength and others. But the concrete has a weakness in the brittle and low tensile strength, so that the concrete construction is reinforced to overcome in the tensile. Then needed a special concrete to increase the tensile strength or strong bending of the fiber concrete. Concrete fibers are concrete with fiber-added materials. In this study, the concrete mixture uses steel-added materials, so it is expected to improve the quality of concrete in general and especially on tensile strength and flexural strength. The steel fibers use 3G Dramix Steel Fiber products with a diameter of 0.75 mm and a length of 60 mm aspect ratio of 80. These tests include on compressive strength, flexural strength and elastic modulus. For testing of compressive strength and elastic modulus using cylindrical test specimen with diameter 15 cm and height 30 cm, while bending strength using plate test object with length 50 cm, width 50 cm and height 5 cm. The cylindrical test specimen consists of sixty cylinders and three plates for each variation. This study used 5 variations, Normal Concrete (N), Normal Concrete plus 10 kg per m3 Steel Fiber (SF10), Normal Concrete plus 20 kg per m3 Steel Fiber (SF20), Normal Concrete plus 30 kg per m3 Steel Fiber (SF30) And Normal Concrete using its rebars. 5mm. From slump testing can be concluded no significant change in the use of steel fiber. And from the compressive strength test, and the bending strength in the plates in obtain the optimum value on Normal Concrete plus 30 kg per m3 (SF30). On Strength Press increased by 11.00% compared to Normal Concrete (N), in Elasticity Modulus was increased compared to Normal and Strong Concrete Strength on plate increased compared to Normal Concrete (N). Â Keywords: Fiber Concrete, Stell Fiber, Strong Press, Modulus of Elasticity, Strong Bending.